MicroRNA-34a-5p: A pivotal therapeutic target in gallbladder cancer - Takashi Oda; Koichiro Tsutsumi; Taisuke Obata; Eijiro Ueta; Tatsuya Kikuchi; Soichiro Ako; Yuki Fujii; Tatsuhiro Yamazaki; Daisuke Uchida; Kazuyuki Matsumoto; Shigeru Horiguchi; Hironari Kato; et al. (Molecular Therapy: Oncology)
Gallbladder cancer incidence has been increasing globally, and it remains challenging to expect long prognosis with the current systemic chemotherapy. We identified a novel nucleic acid-mediated therapeutic target against gallbladder cancer by using innovative organoid-based gallbladder cancer models generated from KrasLSL-G12D/+; Trp53f/f mice. Using comprehensive microRNA expression analyses and a bioinformatics approach, we identified significant microRNA-34a-5p downregulation in both murine gallbladder cancer organoids and resected human gallbladder cancer specimens. In three different human gallbladder cancer cell lines, forced microRNA-34a-5p expression inhibited cell proliferation and induced cell-cycle arrest at the G1 phase by suppressing direct target (CDK6) expression. Furthermore, comprehensive RNA sequencing revealed the significant enrichment of gene sets related to the cell-cycle regulators after microRNA-34a-5p expression in gallbladder cancer cells. In a murine xenograft model, locally injected microRNA-34a-5p mimics significantly inhibited gallbladder cancer progression and downregulated CDK6 expression. These results provide a rationale for promising therapeutics against gallbladder cancer by microRNA-34a-5p injection, as well as a strategy to explore therapeutic targets against cancers using organoid-based models, especially for those lacking useful genetically engineered murine models, such as gallbladder cancer.